Implementation of the 2013 Curriculum at the Elementary School Level - Aisy, Tamara Bishofa'il; Khayati, Imaya Syifaul; Zesa S, Alvina Marissa (Prosiding University Research Colloquium, 2021)
Implementation of the 2013 curriculum is a challenge for the world of education. The 2013 curriculum is very different from the previous curriculum. The approach taken in learning the 2013 curriculum is to use a scientific approach where students are the center of learning. There are three assessment aspects of the 2013 curriculum, namely cognitive aspects (knowledge, psychomotor and attitudes. This research is a qualitative descriptive study. Primary data sources were obtained from observations and interviews with elementary school teachers. The results of the study were analyzed and explained using words. The results showed that some elementary schools have implemented the 2013 curriculum in school learning. Although there are obstacles in its application, the schools are trying their best to achieve the goals of the 2013 curriculum. The 2013 curriculum uses integrative thematic learning methods, scientific approaches, and also authentic assessment.